Influence of seesaw permanent movement of a person on the performance of an air curtain device - Neto, Luís (2006)
In commercial and industrial activities, there is often a need for reducing or controlling heat and mass transfer between outside environment and indoor compartments with controlled atmosphere, warranting, simultaneously, an easy circulation of people and equipments. In practical terms, the confinement of a given space can be achieved with aerodynamic barriers (air curtains) constituted by one or more air jets. In the present paper, the loss of efficiency of a vertical downward air curtain due to the seesaw permanent movement of a person is analyzed. Results show a systematic loss of the sealing efficiency (10 to 20%) of the air curtain device when the doorway is periodically crossed by a computer controlled manikin “Roberta” relatively to the results obtained without this traversing movement.